Mapping of copper oxidation state using high pressure x-ray photoelectron spectroscopy - Kowalska, J.; Gopinath, Chinnakonda S. (Acta Physica Polonica A, 2014)
The interaction of O-2 with polycrystalline foil of Cu, from ultra high vacuum to 1 mbar and up to 773 K has been investigated. The study were performed by using the high pressure X-ray photoelectron spectroscopy (electron spectroscopy for chemical analysis) ultraviolet photoelectron spectroscopy system. In this work the results of mapping copper oxidation states as a function of temperature at 1 mbar O-2 have been presented.